Contribution of crop residues to yield and nutrient uptake of irrigated rice ( Oryza sativa) in rice-rice cropping system - Surekha, K; Reddy, K. Pavan Chandra (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted at Directorate of Rice Research experimental farm, ICRISAT campus, Patancheru, Hyderabad, during 1998-2000 on a sandy clay loam soil (deep Aquic Ustorthent) for 5 consecutive seasons (3 wet and 2 dry) under 5 treatments, viz T1, 100% straw incorporation; T2, 50% straw incorporation; T3, 100% straw + green manure incorporation; T4, 100% straw burning and T5, straw removal to evaluate the effect of different crop residue management practices on grain and straw yields and major nutrients uptake (N, P and K) by rice (Oryza sativa) in rice-rice cropping sequence.Grain yields of rice were significantly influenced by the different crop residue management practices from the third season of residue incorporation, while the nutrients uptake was influenced from second season onwards. During wet season 2000, 11–26%/ increase in grain yield owing to crop residue management was observed with maximum value in straw + green manure treatment. During dry season 2000, the increase was 15-19%, maximum being under burning treatment. The wet season added straw + green manure showed significant residual effect on the yield (17% more) and nutrients uptake (35, 55 and 37% NPK respectively) of dry season rice. The increased nutrients uptake resulted in significant increase (0.34-0.82 and 0.98-1.18 tonnes/ha in wet and dry seasons respectively) in rice productivity which was clear from the correlation between grain yield and nutrients uptake (r=0.65**-0.91** and r=0.55*-0.96* during wet and dry seasons respcctively). Incorporation of rice straw either alone or in combination with green manure and straw burning increased the yields (0.56-1.08 tonnes/ha) through improved nutrients uptake.